PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN MEMBACA PUISI SISWA KELAS X SMA - Marlianda, Rendi; Harjono, Hary Soedarto; Rustam, Rustam (Universitas Hamzanwadi, 2022)
This study aims to determine whether there is an effect of using audio-visual media on the ability of students to read poetry in class X SMA. Sampling in this study used a purpose sampling technique. This research design is pretest posttest control group only design. The research design uses a 2x2 factor. This research method is quasiexperimental or quasi-experimental. Sources of data in this study were the results of students' motivation and poetry reading ability tests. The results of this study prove that there is a significant effect of using audio visual media on students' poetry reading skills with the results of hypothesis testing the value of t count = 3.156 > t table = 1.710 so that the null hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted. Hypothesis 2 test shows that the use of audio-visual media on highly motivated students has a significant effect, this is indicated by the value of tcount = 3.676 > ttable = 1.782. Hypothesis test 3 shows a significant effect of using audiovisual media on low-motivated students as indicated by the value of tcount = 2,572 > ttable 1,782. Hypothesis test 4 shows that there is a significant effect of learning motivation on the ability to read poetry with the value of t count = 2,399 > t table 1,710. This study proves that the use of audio-visual media has a better influence on students' poetry reading skills so that it can be used as an alternative learning that can be applied in the classroom.Keywords: Audio Visual Media, Learning Motivation, Poetry Reading Ability